The Value System and Locus of Control in Students - Sakač, Marija D.; Marić, Mia R. (Sociološki pregled, 2019)
Dealing with the analysis of the values and locus of control, the questionnaire for measuring internal locus of control and the scale for measuring preferences of lifestyles was applied on the sample of 1,146 students. The results confirmed the relation of the value orientations and locus of control in students and pointed out statistically significant differences in students from different faculties regarding lifestyle and internal locus of control. It was confirmed that, according to the lifestyle variable, students of theology show statistically different results from other students. Domination and religiousness bring about this difference to the highest level. The results of analyses in the area of internal locus of control suggest that students from the Faculty of Theology are significantly different from the others in relation to the passive strategy of facing problems.